Snow accumulation variability on a West Antarctic ice stream observed with GPS reflectometry, 2007–2017. Issue 15 (5th August 2017) - Siegfried, M. R.; Medley, B.; Larson, K. M.; Fricker, H. A.; Tulaczyk, S.
Abstract: Land ice loss from Antarctica is a significant and accelerating contribution to global sea level rise; however, Antarctic mass balance estimates are complicated by insufficient knowledge of surface mass balance processes such as snow accumulation. Snow accumulation is challenging to observe on a continental scale and in situ data are sparse, so we largely rely on estimates from atmospheric models. Here we employ a novel technique, GPS interferometric reflectometry (GPS‐IR), to measure upper (<2 m) firn column thickness changes across a 23‐station GPS array in West Antarctica. We compare the results with antenna heights measured in situ to establish the method's daily uncertainty (0.06 m) and with output from two atmospheric reanalysis products to categorize spatial and temporal variability of net snow accumulation. GPS‐IR is an effective technique for monitoring surface mass balance processes that can be applied to both historic GPS data sets and future experiments to provide critical in situ observations of processes driving surface height evolution. Key Points: We apply a method established in Greenland to measure Antarctic snow accumulation at daily resolution from GPS data We compare results from a 23‐station array with in situ data and surface fields from two state‐of‐the‐art atmospheric reanalysis products We suggest that historic ice sheet GPS records could be revisited and that future research should be designed considering this application